Potentiating effect of UVA irradiation on anticancer activity of Carboplatin derivatives involving 7-azaindoles - Štarha, Pavel; Trávníček, Zdeněk; Dvořák, Zdeněk; Radošová-Muchová, Tereza; Prachařová, Jitka; Vančo, Ján; Kašpárková, Jana (PloS one, 2015)
The moderate-to-high in vitro cytotoxicity against ovarian A2780 (IC50 = 4.7-14.4 μM), prostate LNCaP (IC50 = 18.7-30.8 μM) and prostate PC-3 (IC50 = 17.6-42.3 μM) human cancer cell lines of the platinum(II) cyclobutane-1,1'-dicarboxylato complexes [Pt(cbdc)(naza)2] (1-6; cbdc = cyclobutane-1,1'-dicarboxylate(2-); naza = halogeno-substituted 7-azaindoles), derived from the anticancer metallodrug carboplatin, are reported. The complexes containing the chloro- and bromo-substituted 7-azaindoles (1, 2, and 4-6) showed a significantly higher (p < 0.05) cytotoxicity against A2780 cell line as compared to cisplatin used as a reference drug. Addition of the non-toxic concentration (5.0 μM) of L-buthionine sulfoximine (L-BSO, an effective inhibitor of γ-glutamylcysteine synthase) markedly increases the in vitro cytotoxicity of the selected complex 3 against A2780 cancer cell line by a factor of about 4.4. The cytotoxicity against A2780 and LNCaP cells, as well as the DNA platination, were effectively enhanced by UVA light irradiation (λmax = 365 nm) of the complexes, with the highest phototoxicity determined for compound 3, resulting in a 4-fold decline in the A2780 cells viability from 25.1% to 6.1%. The 1H NMR and ESI-MS experiments suggested that the complexes did not interact with glutathione as well as their ability to interact with guanosine monophosphate. The studies also confirmed UVA light induced the formation of the cis [Pt(H2O)2(cbdc`)(naza)] intermediate, where cbdc` represents monodentate-coordinated cbdc ligand, which is thought to be responsible for the enhanced cytotoxicity. This is further supported by the results of transcription mapping experiments showing that the studied complexes preferentially form the bifunctional adducts with DNA under UVA irradiation, in contrast to the formation of the less effective monofunctional adducts in dark.
Keywords: Indoles; indoly; Cell Line, Tumor; protonová magnetická rezonanční spektroskopie; Neoplasms; Proton Magnetic Resonance Spectroscopy; nádory; Molecular Structure; lidé; Buthionine Sulfoximine; adukty DNA; Antineoplastic Agents; protinádorové látky; Ultraviolet Rays; Nucleic Acid Conformation; Carboplatin; DNA Breaks, Double-Stranded; konformace nukleové kyseliny; hmotnostní spektrometrie s elektrosprejovou ionizací; molekulární struktura; DNA Adducts; Drug Synergism; karboplatina; dvouřetězcové zlomy DNA; synergismus léků; Cell Survival; buthionin sulfoximin; viabilita buněk; Spectrometry, Mass, Electrospray Ionization; nádorové buněčné linie; ultrafialové záření; Humans